2021
DOI: 10.1109/access.2021.3049896
|View full text |Cite
|
Sign up to set email alerts
|

LSTM and Filter Based Comparison Analysis for Indoor Global Localization in UAVs

Abstract: Deep learning (DL) based localization and Simultaneous Localization and Mapping (SLAM) has recently gained considerable attention demonstrating remarkable results. Instead of constructing handcrafted algorithms through geometric theories, DL based solutions provide a data-driven solution to the problem. Taking advantage of large amounts of training data and computing capacity, these approaches are increasingly developing into a new field that offers accurate and robust localization systems. In this work, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Although it is difficult for the UAV to perform tasks in indoor environments, studies on SLAM applications for UAV localization in indoor environments have recently increased. In a SLAM study that we previously conducted [100], the results of the previous indoor state-of-the-art visual-inertial SLAM (VISLAM)/visualinertial odometry (VIO) studies and the method that we suggested were compared. With the deep learning-based approach, more successful localization (odometry) was achieved with UAV indoors.…”
Section: Solution Proposal For Uav Applications In Greenhousesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is difficult for the UAV to perform tasks in indoor environments, studies on SLAM applications for UAV localization in indoor environments have recently increased. In a SLAM study that we previously conducted [100], the results of the previous indoor state-of-the-art visual-inertial SLAM (VISLAM)/visualinertial odometry (VIO) studies and the method that we suggested were compared. With the deep learning-based approach, more successful localization (odometry) was achieved with UAV indoors.…”
Section: Solution Proposal For Uav Applications In Greenhousesmentioning
confidence: 99%
“…The development of such applications will also make a significant contribution to smart greenhouses in the future. [100].…”
Section: Solution Proposal For Uav Applications In Greenhousesmentioning
confidence: 99%
“…Camera-based localization approaches have gained much popularity because of providing valuable information about any object/environment, explored by the robotic devices such as aerial vehicles and drones, with low-cost implementations and easy hardware setup [36]. SLAM mechanism is one of those localization approaches which performs both localization and mapping, as the name suggests [37] and used in applications such as virtual and augmented reality [38].…”
Section: ) Simultaneous Localization and Mapping (Slam)mentioning
confidence: 99%
“…DL-based algorithms have proven to be effective in performing identification of the object/environment, classification of the image data and semantic segmentation [36], [39]. These algorithms help in addressing problems such as the instability of the system operations generated from the pose estimation of the camera (due to this being affected by the vibration of the mobile bodies, brightness of the scene etc.)…”
Section: ) Simultaneous Localization and Mapping (Slam)mentioning
confidence: 99%
“…Numerous innovative solutions have been proposed, encompassing VLC-based indoor positioning, multisensory fusion leveraging extended Kalman filters, optical flow-centric systems, and the data amalgamation of the ultrawideband (UWB) and IMU [ 13 , 14 , 15 , 16 ]. Notably, deep learning has recently emerged as a favored solution [ 17 ].…”
Section: Introductionmentioning
confidence: 99%